Timanoplastia Myringoplasty Type 1 and in Residency Surgical Results and Audiometric - Sirena, Edgar; Carvalho, Bettina; Buschle, Mauricio; Mocellin, Marcos (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The tympanoplasty aims to reconstruct the tympanic membrane, restoring protection to the middle ear and improve hearing. In this study we evaluated the surgical results and audiometric this surgery, performed in the service of Otorhinolaryngology, HC / UFPR by residents of the second year in the year 2008 and factors that may influence the results.Method: A retrospective study through review of medical records.Results: Among the 31 patients evaluated, there was closure of the perforation in 24 (80%) and hearing improvement with reduction or closure of the conductive gap by 60% and 26.7% respectively.Discussion: The success rate of surgery was satisfactory and similar to that found in the literature, and factors such as age, presence of unilateral or bilateral pathology and size of perforation were not determinants of surgical success.Conclusion: Tympanoplasty performed by residents of the second year of residence showed satisfactory results regarding both surgical audiometric.
Keywords: audiometry; treatment outcome; tympanoplasty; tympanic membrane